Adaptation of the Missing Scan Task to a touchscreen format for assessing working memory capacity in children. Issue 6 (25th October 2021) - Renner, Elizabeth; Somai, Rosyl S.; Van der Stigchel, Stefan; Campbell, Clare; Kean, Donna; Caldwell, Christine A.
Abstract: Assessing children's working memory capacity (WMC) can be challenging for a variety of reasons, including the rapid increase in WMC across early childhood. Here, we developed and piloted an adapted WMC task, which involved minimal equipment, could be performed rapidly, and did not rely on verbal production ability (to facilitate the use of the task with younger children). In our adaptation, we portrayed the events of the object‐based Missing Scan Task (creatures hiding in and emerging from a house) in a touchscreen format. In the full experiment, 67 participants aged 23 to 90 months achieved the longest set size (LSS) scores that were distributed across the full range of possible scores. A comparison of these scores with those obtained using object‐based formats indicated general agreement between the versions of the task. Scores were found to increase with child age. We propose this (freely available) touchscreen adaptation as a suitable WMC task for use with children aged 2 to 7 years.